نظمِ قرآن اور اس کے مترادفات :تجزیاتی مطالعہ: Qur’anic Structure and its Terminological Equivalents: A Critical Analysis - Zakir Hashmi, Dr. Muhammad; Najeeba kanwal, Najeeba kanwal (Al-Amīr Research Journal for Islamic Studies, 2024)
The divine arrangement of the Holy Qur’an suggests a profound connection between its sentences, verses (‘ayaat’), and chapters (‘surahs’). This connection, however, is not explicitly stated (’mansoos’) but is derived through scholarly interpretation (’ijtihadi’), which is why varying opinions exist on the matter. Scholars have used various terms to describe this connection, including ‘nazm’ (order), ‘wahdat’ (unity), ‘rabt’ (connection), ‘munasibat’ (appropriateness), and ‘tanasuq’ (proportion). This article presents an analytical study of these terms, concluding that the concept of structure within the Qur’an is represented by four primary synonyms: ‘tanasuq’ (proportion), ‘tawafuq’ (agreement), ‘rubt’ (structure), and ‘irtibat’ (correlation), with ‘munaasibat’ (relevance) and ‘tanasub’ (correspondence) being closely related. Prominent scholars such as Jahiz, Ibn Qutayba, Wasti, Jurjani, Farahi, and Nursi have frequently employed the term "structure" to explore the artistic, internal, rhetorical, and literary coherence within the ayaat and surahs. While Nursi’s perspective aligns with this structural approach, Farahi uniquely expands the concept to include both the structural and systematic interrelationships between the verses and chapters. Scholars who have examined the interrelationship of verses within surahs often prefer the terms "relevance" or "connection." It is important to note that there is a nuanced distinction between "tawafuq" (agreement) used for the correspondence of verses and other terms. Additionally, while "taleef" (compilation), "tarteeb" (arrangement), and "context" are related concepts, they are not synonymous with the structural analysis discussed here. Keywords: Poetic Unity, Synonyms, Qur’an, Analysis, Relevance, Superficiality.